Effects of a rational-emotive health education intervention on stress management and irrational beliefs among technical college teachers in Southeast Nigeria. Issue 31 (August 2017) - Ugwoke, Samuel C.; Eseadi, Chiedu; Igbokwe, Chima C.; Chiaha, Gertrude T.U.; Nwaubani, Okechukwu O.; Orji, Chibueze Tobias; Ugwuanyi, Leonard T.; Chukwuma, Ifeoma S.; Edikpa, Edith C.; Ogakwu, Vera N.; Onu, Eucharia A.; Agu, Patricia; et al.
Abstract: Background: Stress is the product of how an individual reacts and adapts to the specific demands and threats they encounter while carrying out given tasks. The main purpose of this study was to investigate the effects of a rational-emotive health education intervention (REHEI) on stress management, and irrational beliefs in a sample of technical college teachers in Southeast Nigeria. Method: The study design was a pretest–posttest control group. Repeated measures analysis of variance, paired t test and Mann–Whitney U tests were used to analyze the data collected. Results: The REHEI significantly reduced teacher stress in those teaching staff exposed to the treatment intervention, relative to a waitlist control group. Furthermore, the REHEI program significantly decreased irrational beliefs about teaching in those teaching staff exposed to the treatment intervention compared to a waitlist control group. Conclusion: The REHEI program can be used to coach teachers on how to manage and cope with stress and overcome irrational beliefs in teaching.